Neural activity in relation to empirically derived personality syndromes in depression using a psychodynamic fMRI paradigm - Taubner, Svenja; Wiswede, Daniel; Kessler, Henrik (Frontiers in Human Neuroscience, 2013)
Objective: The heterogeneity between patients with depression cannot be captured adequately with existing descriptive systems of diagnosis and neurobiological models of depression. Furthermore, considering the highly individual nature of depression, the application of general stimuli in past research efforts may not capture the essence of the disorder. This study aims to identify subtypes of depression by using empirically-derived personality-syndromes, and to explore neural correlates of the derived personality syndromes. Method: In the present exploratory study an individually tailored and psychodynamically based fMRI paradigm using dysfunctional relationship patterns was presented to 20 chronically depressed patients. Results from the Shedler-Westen-Assessment-Procedure (SWAP-200) were analyzed by Q-factor analysis to identify clinically relevant subgroups of depression and related brain activation. Results: The principle component analysis of SWAP-200 items from all 20 patients lead to a 2-factor solution: “Depressive Personality” and “Emotional-Hostile-Externalizing Personality”. Both factors were used in a whole-brain correlational analysis but only the second factor yielded significant positive correlations in four regions: A large cluster in the right orbitofrontal cortex (OFC), the left ventral striatum, a small cluster in the left temporal pole and another small cluster in the right middle frontal gyrus. Discussion: The degree to which patients with depression score high on the factor “Emotional-Hostile-Externalizing Personality” correlated with relatively higher activity in three key areas involved in emotion processing, evaluation of reward/punishment, negative cognitions, depressive pathology and social knowledge (OFC, ventral striatum, temporal pole). Results may contribute to an alternative description of neural correlates of depression showing differential brain activation dependent on the extent of specific personality syndromes in depression.